1995
DOI: 10.1108/02651339510097757
|View full text |Cite
|
Sign up to set email alerts
|

Do not‐for‐profits value their customers and their needs?

Abstract: Not‐for‐profit organizations, sometimes called charities or voluntary organizations, are assumed to be serving their customers well – but are they? A customer segmentation is proposed of beneficiaries, supporters, stakeholders and regulators, each group having intermediaries through which the end customer may be reached. Lays out structural reasons why not‐for‐profits may not value or respect their customers, including excess demand, lack of competition, professional dominance and distance, lack of consumer re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 1 publication
1
48
0
Order By: Relevance
“…A donor priority strategy supports simultaneous increases in donor satisfaction, leading to high levels of donor loyalty. This finding helps clarify prior work, with its mixed results regarding whether a priority strategy affects all donor groups positively (Bruce 1995;Homburg et al 2008). We also can posit some possible reasons for this finding.…”
Section: Discussion and Managerial Implicationssupporting
confidence: 44%
See 1 more Smart Citation
“…A donor priority strategy supports simultaneous increases in donor satisfaction, leading to high levels of donor loyalty. This finding helps clarify prior work, with its mixed results regarding whether a priority strategy affects all donor groups positively (Bruce 1995;Homburg et al 2008). We also can posit some possible reasons for this finding.…”
Section: Discussion and Managerial Implicationssupporting
confidence: 44%
“…However, a donor priority strategy also might have negative effects (Harrison-Walker 2010;Homburg, Droll, and Totzek 2008). Lower priority donors might express reduced satisfaction or even become dissatisfied, then spread negative word of mouth about or end their relationship with the nonprofit organization (Bruce 1995). In addition, the strategy might incur higher fundraising costs, because many donors would donate even if no benefits were offered (Granik 2005).…”
mentioning
confidence: 98%
“…These techniques and approaches have been recognized as important to non-profits by the academic field (Gonzalez et al, 2002); one in particular is especially important -the marketing concept -which advocates an understanding of the customer (Day, 1994). It appears, however, that the competitive advantages that could be gained from using the full portfolio of the marketing toolbox are not harvested as successfully as they could be (Bruce, 1995). Instead of embracing the marketing concept and beginning the marketing process with the customer and investigating what the market actually needs and wants (Gonzalez et al, 2002), non-profit organizations have an "organizationcentered" marketing mindset and may falsely believe that their product or service is needed by the market (Andreasen and Kotler, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Due to these indicators, it was suggested that marketing had a great deal to offer the third sector in order to "survive, grow, and strengthen their contributions to the general welfare" (Kotler, 1979, p. 44). Complicating characteristics of non-profits' organizational structure include non-financial objectives, multiple stakeholders (Bruce, 1995), a competitive-collaborative relationship with other organizations in the field, and the balance between financial pressures and the mission (Gallagher and Weinberg, 1991). These characteristics make it very difficult to ascertain success and may lead to their disregard of marketing.…”
Section: The Adoption Of Marketing By Non-profit Organizationsmentioning
confidence: 99%
“…Some argue that this has not gone far enough; for example, Bruce states, 'What is needed is a greater adoption of a marketing approach in not-forprofit organizations'. 4 Others however, are more skeptical and Graham 5 comments, 'Despite the ambitious claims of the discipline, the transposition of marketing to THE NONPROFIT SECTOR There seems to be a general consensus that the role of marketing in the modern economy has increased, and Levy and Zaltman 6 go so far as to say that it has 'burgeoned dramatically in recent years'. There has also been an increase in the size of the nonprofit sector, and the number of nonprofit organisations has trebled in the United States in the last three decades.…”
Section: Introductionmentioning
confidence: 94%